Substitution-based linguistic steganography based on antonyms - Fawwaz Zamir Mansor; Azizan Ismail; Roshidi Din; Aida Mustapha; Noor Azah Samsudin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The study of steganography focuses on strengthening the security in protecting content message by hiding the true intention behind the texts. However, existing linguistic steganography approach especially in synonym-based substitution is prone to attack. In this paper, a new substitution-based approach for linguistic steganography is proposed using antonyms. The antonym-based stego-text generation algorithm is implemented in a tool called the Antonym Substitution-based (ASb). Evaluation of ASb was carried out via veriﬁcation and validation. The results showed highly favorable performance of this approach.